Gender Equity in M-19 Combat, Colombia, South America, 1970-1989 - Wakeland, R.G. (International Journal of Culture and History, 2024)
Between 1970 and 1989 the M-19 guerrilla group in Colombia, South America sought regime change via armed conflict. Interviews and autobiographies as well as government and military observations of engagements involving weapons provided sources for a gender role analysis. The author argued that male and female M-19 individuals adopting arms participated in gender equity. Although there were statistically greater numbers of male than female combatants and authoritarian figures in combat, decisions to perpetrate armed violence were autonomous and suicidal. Women as well as men were given equal opportunity to kill and be killed. M-19 elevated anyone who carried a weapon to equal status of liberator in the model of Simon Bolívar, towards its goal of a second national liberation. A literature review presented other theories and conclusions of gender roles among M-19.